Biological CNP removal from meat-processing wastewater in an innovative high rate up-flow A2O bioreactor. (December 2018) - Abyar, Hajar; Younesi, Habibollah; Bahramifar, Nader; Zinatizadeh, Ali Akbar
Abstract: A high rate up-flow anaerobic, anoxic and oxic (A2 O) bioreactor was designed and operated for meat-processing wastewater (MPW) treatment as a single cost-effective system with the aim of simultaneous CNP removal. The influence of three essential factors, HRT, COD/TN ratio and aerated volume fraction on the reactor performance was assessed using response surface methodology (RSM). The required HRT to reach 98.5% COD removal was achieved at 7.5 h. Simultaneous CNP removal under denitrification rate of 199.4 mg/l.d gave high nitrate to nitrogen gas conversion of 74.6 mg/l. An HRT, COD/TN ratio and aerated volume fraction of 10 h, 100:20 and 60%, respectively, was a favored condition for an efficient nitrogen removal with effluent total Kjeldahl nitrogen (TKN) less than 70 mg/l. Under optimum condition, an HRT, COD/TN and aerated volume fraction of 8 h, 100:14 and 65%, respectively, resulted an effluent phosphorus of 43 mg/l, but 93.97 mg/l phosphorus was released in an anaerobic condition at 6 h. An effluent with a low turbidity of about 1.5 NTU and a sludge volume index (SVI) of 75.9 ml/g was achieved using at HRT of 12.5 h, COD/TN ratio of 100: 8 and aerated volume fraction of 50%. Under these conditions, the removal efficiencies for COD, TKN, nitrate-nitrogen (NO3 − -N), total nitrogen (TN) and phosphorus (PO4 3- -P) were obtained to be 98.33, 92.06, 91.97, 90.48 and 83.48%, respectively. As a result, the application of the up-flow A2 O bioreactor is a promising configuration to get hygienic water from wastewater. Graphical abstract: Highlights: The performance of anaerobic, anoxic and aerobic (A2 O) bioreactor is evaluated. High rate simultaneous nutrient removal in a single A2 O is studied. The effects of process variables are optimized using response surface methodology. Statistical models are used to develop mathematical depictions of nutrient removal. The study shows the benefits of using A2 O for meat processing wastewater treatment.